Investigando as atitudes dos docentes do ensino básico que vêm influenciando negativamente a imagem da disciplina de Física - Pastorini, Rosângela Centuário (2013)
In this investigation we had class observations of Physics teachers, and apllied a questionnaire having multiple choices questions and opening to the students, focusing identification of teachers attitudes which would be contributing to the professional rejection for the career of Physics teaching,. identified in other researches.. We visited public and private schools of seventeen regions from Porto Alegre borough, one at each region, total of seventeen teachers observed and almost two hundred forty students replied of that questionnaire . The observations had phenomenological characteristics and the information taken were analysed and the results suggest that the most meaningful negative attitudes refer to the teachers attitude, which imposes such a dynamic that their classes seem to be a complement or application of Mathematics, giving small interest to students on keeping learning Physics out of school s and consequently following the career as teachers of this science. We realized that teachers seem to be uninterested in relation to activity that accomplishes of manual way, acting of traditional-displayed way discontextualized and without experimentation, no matter the kind of school, of material conditions and the existent salaries.